Analisis Efisiensi dan Pendapatan Usaha Tani Padi Sawah - Ir. Cyprianus P.H. Saragi, MS; Marwanti Lase, Enjelyn (Universitas Katolik Santo Thomas Medan, 2025)
This research aims to 1) To find out what production factors influence the production of lowland rice farming in the research area, (2) To find out the level of allocative efficiency in the use of production factors in lowland rice farming, (3) To find out the amount of net income per hectares/planting season for lowland rice farming. The research was conducted in Soewe Village, Gido District, Nias Regency, which was determined purposively. Sampling was carried out using the census method with a sample size of 38 families. From the research results, the following conclusions were obtained: (1) Simultaneously, the use of seed production factors, urea fertilizer, NPK fertilizer, Kresna pesticide and labor have a real/significant effect on the production of lowland rice farming. Partially, the use of seed production factors, urea fertilizer, NPK fertilizer, and Kresna pesticides has a significant effect on lowland rice production, while labor has no real/significant effect on lowland rice farming production, (2) Use of seed production factors, urea fertilizer, NPK fertilizer , and Kresna pesticides are not yet efficient, meaning that the use of these production factors can still be increased in order to increase the production of lowland rice farming, while labor is inefficient, meaning that the use of these production factors needs to be reduced in order to increase the production of lowland rice farming, (3) The research results show The net income obtained by lowland rice farmers in Soewe Village, Gido District, Nias Regency is IDR 14,076,303/ha/mt.